2004
DOI: 10.1002/ardp.200400881
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Molluscicidal Activity of 5‐oxo‐5,6,7,8‐Tetrahydro‐4H‐Chromene Derivatives

Abstract: Furfurylidenemalononitriles and thienylidenemalononitriles were treated with 1,3-cyclohexanediones to afford 2-amino-4-hetaryl-5-oxo-5,6,7,8-tetrahydro-4H-chromene-3-carbonitrile derivatives. The molluscicidal activity of these compounds was investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 91 publications
(54 citation statements)
references
References 14 publications
5
49
0
Order By: Relevance
“…The phenyl analog 13b is far less active (LC 90 = 14 ppm), while the 3-thienyl derivatives 13c, d are seldom active. These results confirm our previous observations [7]. A comparison of the molluscicidal activity of the new compounds reported here with the international standard 29,5-dichloro-4-nitrosalicylanilide (LC 100 = 1 ppm) [4,5] showed that our compounds are still far inferior as molluscicidal agents.…”
Section: Molluscicidal Activitysupporting
confidence: 90%
See 3 more Smart Citations
“…The phenyl analog 13b is far less active (LC 90 = 14 ppm), while the 3-thienyl derivatives 13c, d are seldom active. These results confirm our previous observations [7]. A comparison of the molluscicidal activity of the new compounds reported here with the international standard 29,5-dichloro-4-nitrosalicylanilide (LC 100 = 1 ppm) [4,5] showed that our compounds are still far inferior as molluscicidal agents.…”
Section: Molluscicidal Activitysupporting
confidence: 90%
“…[10,11]. 3-Furfurylidene/thienylidene-malononitrile derivatives 11a and 11b were prepared according to the method reported in our previous paper [7].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example Bergapten 1 [1,2]; ricchiocarpin A 2, and ricchiocarpin B 3 [3], the chromene derivative 4 [4] and the pyranopyrazole 5 [5] (Fig. 1); all have shown a considerable molluscicidal activity.…”
Section: Introductionmentioning
confidence: 99%